Ultrahigh-pressure liquid chromatography of isoflavones and phenolic acids on different stationary phases - Klejdus, B; Vacek, J; Lojková, L; Benesová, L; Kubán, V (Journal of chromatography. A, 2008)
Complete separation of aglycones and glucosides of selected isoflavones (genistin, genistein, daidzin, daidzein, glycitin, glycitein, ononin, sissotrin, formononetin, and biochanin A) was possible in 1.5 min using an ultrahigh-pressure liquid chromatography (U-HPLC) on a different particular chemically modified stationary phases with a particle size under 2 microm. In addition, selected separation conditions for simultaneous determination of isoflavones together with a group of phenolic acids (gallic, protocatechuic, p-hydroxybenzoic, vanillic, caffeic, syringic, p-coumaric, ferulic, and sinapic acid) allowed separation of all 19 compounds in 1.9 min. Separations were conducted on a non-polar reversed phase (C(18)) and also on more polar phases with cyanopropyl or phenyl groups using a gradient elution with a mobile phase consisting of 0.3% aqueous acetic acid and methanol. Chromatographic peaks were characterised using parameters such as resolution, symmetry, selectivity, etc. Individual substances were identified and quantified using UV-vis diode array detector at wavelength 270 nm. Limits of detection (3S/N) were in the range 200-400 pg ml(-1). Proposed U-HPLC technique was used for separation of isoflavones and phenolic acids in samples of plant materials (Trifolium pratense, Glycine max, Pisum sativum and Ononis spinosa) after acid hydrolysis of the samples and modified Soxhlet extraction.
Keywords: isoflavony; hrách setý; Glycine max; Hydroxybenzoates; Pisum sativum; Chromatography, High Pressure Liquid; rostlinné extrakty; Caffeic Acids; Plant Extracts; Molecular Structure; Genistein; molekulární struktura; propionáty; Gallic Acid; Propionates; kyselina vanilová; Coumaric Acids; genistein; hydroxybenzoáty; Trifolium; Vanillic Acid; vysokoúčinná kapalinová chromatografie; kyselina gallová; kyseliny kávové; kyseliny kumarové; Isoflavones